Student engagement in low-income, high-stress learning environments - Sitzer, Bradwin (Graduate School of Business (GSB), 2021)
This study analyses the level of student engagement at youth skills development organisations which are situated in low-income, high-stress communities. It asks the following questions: What motivates youth to be engaged in their learning environments? What are youths reporting on experiencing while in the learning environment? How might we use this data to help us develop the skills of the youth better? Through capturing a day in the life of youth from a cognitive, emotional and contextual point of view, we are better able to understand what drives youth to learn and achieve. Eight themes were identified which influenced the students to be highly engaged according to Flow Theory. An important context to be taken into account in the design of learning environments for youth is the psychological impact of living in a high-stress community. An emergent case for self-managed Flow is presented, where students drive and hold themselves accountable for high levels of engagement around the eight themes.